Pengaruh Kualitas Produk, Promosi dan Persepsi Harga Terhadap Keputusan Pembelian Pakaian di Outfitbycimoi - Sidabalok, Clara Claudia; Sugiyanto, Sugiyanto (Jurnal Ilmiah Wahana Pendidikan, 2023)
The main objective of this research is to see how the influence of product quality, promotion and price perceptions on the decision to purchase clothes at Outfitbycimoi for online and offline consumers who are in the Pandeglang-Banten area. The sampling technique used in this research is non-probability sampling with purposive sampling method. The number of respondents used in this study amounted to 200 respondents with criteria aged 17 years and over who had purchased and used Outfitbycimoi products. The analytical method used is multiple linear analysis. The results and findings in this study indicate that Product Quality influences the decision to purchase Outfitbycimoi clothing, Promotion does not affect the decision to purchase Outfitbycimoi clothing and Price Perception influences the decision to purchase Outfitbycimoi clothing.